2009
DOI: 10.1007/s11661-009-0033-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclic Thermal Process on Ultrafine Grain Formation in AISI 304L Austenitic Stainless Steel

Abstract: As-received hot-rolled commercial grade AISI 304L austenitic stainless steel plates were solution treated at 1060°C to achieve chemical homogeneity. Microstructural characterization of the solution-treated material revealed polygonal grains of about 85-lm size along with annealing twins. The solution-treated plates were heavily cold rolled to about 90 pct of reduction in thickness. Cold-rolled specimens were then subjected to thermal cycles at various temperatures between 750°C and 925°C. X-ray diffraction sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In a more recent study, Sun et al [140] reported that in two-stage annealing of a 304 ASS containing 47% DIM and 53% DA after two-stage cold rolling (67% + 47%, respectively) at 800 and 850 • C, non-uniform grain structure was created, where the fraction of ultrafine grains (<1 µm) decreased and larger austenite grains (up to 3 µm) increased with prolonged annealing. Ravi Kumar et al [18,146,147] and Ravi Kumar and Raabe [148] have obtained bulk ultrafine-grained ASS with mono-(maximum at GS ≈ 0.6 µm) and bimodal-type (minimum at GS ≈ 0.5 µm and maximum at GS ≈ 1.40-1.65 µm) GS distributions by 4-stage cyclic thermal processing in a 90% cold-rolled AISI 304L grade. This enhanced significantly the elongation.…”
Section: Reversed Microstructuresmentioning
confidence: 99%
“…In a more recent study, Sun et al [140] reported that in two-stage annealing of a 304 ASS containing 47% DIM and 53% DA after two-stage cold rolling (67% + 47%, respectively) at 800 and 850 • C, non-uniform grain structure was created, where the fraction of ultrafine grains (<1 µm) decreased and larger austenite grains (up to 3 µm) increased with prolonged annealing. Ravi Kumar et al [18,146,147] and Ravi Kumar and Raabe [148] have obtained bulk ultrafine-grained ASS with mono-(maximum at GS ≈ 0.6 µm) and bimodal-type (minimum at GS ≈ 0.5 µm and maximum at GS ≈ 1.40-1.65 µm) GS distributions by 4-stage cyclic thermal processing in a 90% cold-rolled AISI 304L grade. This enhanced significantly the elongation.…”
Section: Reversed Microstructuresmentioning
confidence: 99%
“…A schematic illustration of the thermal cycling is presented in the plot of Figure 1 [24]. A short holding period of 1 min at the peak temperature was selected mainly to inhibit the grain growth [20]. Short soaking periods at the annealing temperature of about 1 min are generally recommended for reducing costs from an industrial viewpoint [18,25].…”
Section: Methodsmentioning
confidence: 99%
“…Particularly, the grain boundary angles of most γ grains were concentrated between 53 • and 63 • ; they were not affected by the thermal cyclic number (Figure 6b). It has been reported that newly reverted γ assembles the lath martensite at high-angle boundaries after repeated thermal cycles [20,24]. The complexity increases because of the simultaneous presence of δ and γ phases in DSS.…”
Section: Misorientation Angle Analysismentioning
confidence: 99%
See 2 more Smart Citations